Economic mechanism of management of oil and gas producing enterprise during the exploration of residual reserves of hydrocarbon - Витвицький, Я. С.; Петрунчак, І. М. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
Тhe article describes management economic mechanism of oil and gas enterprises during residual hydrocarbons development. Institutional and organizational, regulatory, geological and geophysical, information, innovation, finance, human resources, motivational support; pricing, tax incentives and total controlling ensuring belong to the elements of the organizational and economic mechanism.Determined that the use of all the structural elements of the mechanism within the enterprise development strategy will increase the efficiency of their activities.